ESTIMASI BEBAN LIMBAH ORGANIK DARI TAMBAK UDANG SUPERINTENSIF YANG TERBUANG DI PERAIRAN TELUK LABUANGE - Paena, Mudian; Syamsuddin, Rajuddin; Rani, Chair; Tandipayuk, Haryati (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2020)
Environmental pollution in the form of organic waste containing nitrogen (N) and phosphate (P) sourced from superintensive shrimp pond cultivation due to much feed use is a severe problem in the development of superintensive technology in Indonesia. This study aims (1) to estimate the amount of feed wasted into the environment during cultivation in superintensive ponds and (2) estimate the amount of N and P waste that is wasted into the environment from superintensive cultivation. The research method is carried out in 3 stages; the first stage was carried out on a superintensive pond for 76 days by carrying out superintensive shrimp farming with a density of 600 tails / m2 then carried out observations of wasted feed. The second stage is to conduct laboratory-scale shrimp digestibility tests, and the third stage is laboratory-scale shrimp excretion research. The results showed that (1) the amount of feed wasted into the environment (un-eaten) amounted to 24.32% of the total feed provided. The burden of organic waste from superintensive ponds shrimp discharged into the waters of Labuange Bay is 3.89 tons/year consisting of organic waste containing N amounting to 3.61 tons/year with a mean of discharging to waters of 10.31 kg/day, and organic waste containing P of 0.28 tons/year with a mean discharge to the waters of 0.81 kg/day. These results indicate that the waters of Labuange Bay have experienced the pressure of organic waste originating from superintensive shrimp pond activities.